OPTIMISATION OF TREATMENT METHODS FOR LARYNGOTRACHEITIS IN CHILDREN (World Bulletin of Public Health, 2022)
Acute stenotic laryngotracheitis (SLT, croup, obstructive laryngitis) is one of the pressing and unresolved problems in pediatrics [1; 2]. Today, croup syndrome is characterized by a high prevalence in childhood, pronounced dynamism of clinical symptoms, the possibility of rapid development of severe bacterial complications and lethal outcome, and an increase in the percentage in favour of recurrent forms of obstructive laryngitis [3-5]. Primary SLT develops during the second or third year of life, less frequently at an older age. More than 30% of patients with obstructive laryngitis relapse within 2 years of the first episode of laryngeal stenosis, often with signs of bronchial obstruction. There is an ongoing discussion about the influence of various factors on the development of recurrent stenotic laryngotracheitis, but no unified point of view can be found in the publications of researchers [6]. In foreign and domestic literature, high-risk criteria for the development of recurrent SLT in children can be found, including concomitant allergopathology, immunological dysfunction, the presence of gastroesophageal reflux, and the occurrence of a first episode of croup before 6 months of age [7; 8]. Premorbid background and comorbid conditions are known to affect the course of acute, especially recurrent and chronic respiratory diseases to a certain extent.
Keywords: Laryngotracheobronchitis; Children Treatment.